Correlation between strength related parameters and ski-jumping performance in junior ski jumpers - Fritz, J.; Lindinger, S. J.; Schwameder, H. (Sciene and nordic skiing III, 2016)
Ski jumping is a complex, competitive sport that includes several phases: In-run, take-off, first flight and stable flight phase, landing preparation and landing. It is well accepted that the take-off is the most challenging phase for a successful jump (Komi & Virmavirta, 1996; Schwameder, 2008; Virmavirta & Komi, 2001a). Take-off has to be performed from a deep crouch position at a very high in-run speed. This phase has to be executed within 250-300 ms (Komi & Virmavirta, 1996). Because of the low friction coefficient between the in-run tracks and the skis, the force can almost exclusively act perpendicular to the surface (Schwameder, 2008). For a successful take-off, the jumper has to gain high vertical release velocity while maintaining the horizontal velocity by keeping the upper body in an aerodynamically beneficial position. In order to reach high vertical release velocities, high knee and hip angular velocities are required (Komi et al., 1974; Schwameder & Müller, 1995; Virmavirta & Komi, 1993). To compensate for the backward rotating angular momentum acting on the jumper-ski system during early flight, the jumper has to produce a forward rotating angular momentum during take-off (Arndt et al., 1995; Schwameder, 2008). It can be concluded that take-off requires high demands on the athlete`s strength and coordination abilities.